Aberrant Mitochondrial Dynamics: An Emerging Pathogenic Driver of Abdominal Aortic Aneurysm - Mingqi Ouyang; Mi Wang; Bilian Yu (Cardiovascular Therapeutics)
Abdominal aortic aneurysm (AAA) is defined as a progressive segmental dilation of the abdominal aorta and is associated with high mortality. The characterized features of AAA indicate several underlying mechanisms of AAA formation and progression, including reactive oxygen species production, inflammation, and atherosclerosis. Mitochondrial functions are critical for determining cell fate, and mitochondrial dynamics, especially selective mitochondrial autophagy, which is termed as mitophagy, has emerged as an important player in the pathogenesis of several cardiovascular diseases. The PARKIN/PARIS/PGC1α pathway is associated with AAA formation and has been proposed to play a role in mitochondrial dynamics mediated by the PINK/PARKIN pathway in the pathogenesis underlying AAA. This review is aimed at deepening our understanding of AAA formation and progression, which is vital for the development of potential medical therapies for AAA.